Massive Parallel Sorting of Particles Using Unwound Polygonal Vortex Beams - Li, Xiaofei; Zhang, Hao; Gao, Yuanmei; Gbur, Greg; Cai, Yangjian; Yuan, Yangsheng (Frontiers in Physics, 2022)
Optical sorting, as one kind of the optical tweezers, is used to separate the mixed particles in a background environment. This unusual tool has a wide application prospect, because the non-contact and nondestructive advantages ideally suit the pressing need of bio-technology. However, most sorting methods and devices have been accomplished based on real-time one-by-one sorting, which ignored the sorting efficiency and is not applicable to high-capacity particle. Although more and more structure light beams are proposed to enhance the sorting efficiency, it is still not enough for desired applications. Here, we propose a method for the massive parallel sorting of particles: polygonal optical vortex (OV) beams are unwound by a geometric transformation to produce linear OV beams with kinked distributions. This structured light is used to greatly enhance the sorting efficiency. We adopt the fractal theory to illustrate the increasing of the region over which the beam can interact with particles. We demonstrate that the gradient force of this beam is large enough to manipulate spherical particles in the Rayleigh regime of scattering. These results introduce new possibilities for high-capacity particle sorting.